2018
DOI: 10.3389/fgene.2018.00466
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Related to Cardiometabolic Traits Are Associated to B Cell Function, Insulin Resistance, and Diabetes Among AmeriCan Indians: The Strong Heart Family Study

Abstract: Background: Genetic research may inform underlying mechanisms for disparities in the burden of type 2 diabetes mellitus among American Indians. Our objective was to assess the association of genetic variants in cardiometabolic candidate genes with B cell dysfunction via HOMA-B, insulin resistance via HOMA-IR, and type 2 diabetes mellitus in the Strong Heart Family Study (SHFS).Methods and Results: We examined the association of variants, previously associated with cardiometabolic traits (∼200,000 from Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…A case-control study from Japan recruited 374 Japanese patients and 375 populationbased controls scanned throughout chromosome 21 to assess genetic associations with late-onset alzheimer's disease and found the marker of the EP gene linked to the SNPs of chromosome 21 in late-onset alzheimer's disease patients (41). Other studies also found that the EP gene may be implicated in Down syndrome, cardiometabolicity and cancer (66)(67)(68). Since the large scope of EP covers diseases and we know little about it, extensive research is still needed to determine its relevance to specific diseases.…”
Section: Ep With Diseases: Congenital Enteropeptidase Deficiency Panc...mentioning
confidence: 99%
“…A case-control study from Japan recruited 374 Japanese patients and 375 populationbased controls scanned throughout chromosome 21 to assess genetic associations with late-onset alzheimer's disease and found the marker of the EP gene linked to the SNPs of chromosome 21 in late-onset alzheimer's disease patients (41). Other studies also found that the EP gene may be implicated in Down syndrome, cardiometabolicity and cancer (66)(67)(68). Since the large scope of EP covers diseases and we know little about it, extensive research is still needed to determine its relevance to specific diseases.…”
Section: Ep With Diseases: Congenital Enteropeptidase Deficiency Panc...mentioning
confidence: 99%